An analysis of the physics achievement of public school teachers in the Division of City Schools, Quezon City - Alvarez, Carmencita Aquino (Animo Repository, 1988)
Primarily, the purpose of the study is to determine the strengths and weaknesses of teachers in the Division of City Schools, Quezon City, in the field of physics in terms of the cognitive skill levels and content areas. Secondarily, the study attempts to compare the physics achievements of teachers to the national norms established by the Philippine Science and Mathematics Council (PSMC), and to determine factors related to physics achievement. All the norms used in the study were taken from the achievement testings in physics conducted by the PSMC during the SY 1982-1983 and that of the public school teachers in the division of City Schools, Quezon City. The answer sheets in physics achievement test and the GZTS of teachers were singled out for the study. Means, medians, and standard deviations were computed from the frequency distributed ungrouped scores. The difficulty indices were determined from the proportions of the subjects answering the items correctly. These difficulty indices were the basis for determining the strengths and weaknesses in physics of the teachers as manifested by the results of their academic achievement test. The physics achievement, as indicated by the scores, was correlated with the following variables: involvement in extra-curricular activity, number of hours teaching physics per week, became a teacher of physics by choice or forced, and with personality, using Pearson's product moment correlation coefficients. Hypotheses were tested at, at least 5 significance level using t-test. The physics teachers were found weak in knowledge, and relatively strong in comprehension and application levels. The same teachers were also found to be strong in the content areas of mechanics, thermodynamics, electro-magnetism, and modern physics but weak in the content areas of optics. The physics achievement of the teachers are significantly higher from the national norms established by PSMC in 1982-83. The physics achievement of the teachers is not significantly related with the following factors: extra-curricular activity, type of physics teacher, number of hours teaching physics per week, and personality traits such as general activity, ascendance, restraint, sociability, objectivity, friendliness, thoughtfulnes, and masculinity. However, it is significantly related with the personality trait, personal relations.